Three-dimensional Cu(OH)2 nanowire for highly efficient and selective uranium extraction from complex wastewater - Shaobin Cheng; Qingyan Zhang; Yifeng Hu; Binsheng He; Lei Shang; Xijun Fu; Yanlin Chen; Tao Cai; Qingyi Zeng (Desalination, 2026)

Duplication and divergence: Two new Dmrt1 gene paralogs identified in autotetraploid Carassius auratus - Qian Xiao; Qingwen Xiao; Xu Huang; Yanlin Fu; Yuhan Yang; Chongqing Wang; Xiaowei Xu; Xidan Xu; Kun Zhang; Yue Zhou; Jinhai Bai; Zhengkun Liu; et al. (Aquaculture, 2026)

Retrieval-assisted feature fusion of SAR image and bounce-coded RCS for aircraft classification - Shangchen Feng; Xikai Fu; Yanlin Feng; Xiaolei Lv (International Journal of Remote Sensing, 2026)

A Theoretical Model for Unsteady-Flow Dewatering by Vertical–Slanted Combination Wells in an Unconfined Aquifer - Qiaosong Fu; Yanlin Li; Liyun Li; Wenjing Li (Transportation Geotechnics, 2026)

Dye displacement on a GO-like cationic porphyrin polymer for heparin sensing and quality control - Yusheng Fan; Yanlin Fu; Chunfei Bao; Weihua Zhang; Yubin Ding (Analytica Chimica Acta, 2026)

Water regime management reduces pest infestations and cadmium content in rice in paddy ecosystems - Yanlin Huang; Dexin Wei; Guizhen Mo; Qixian Fu; Di Yang; Jinlian Liang; Yuhui Peng; Yanyan Wei; Bing He; Minghua Gu; Xueli Wang (Agriculture, Ecosystems & Environment, 2026)

Polypyrrole-modified carbon felt cathode significantly boosts solar-driven Photoelectrocatalysis for enhanced tri-functional uranium recovery, organic pollutant degradation, and electricity generation - Yunjiao Hao; Xijun Fu; Xuefang Chen; Qingyan Zhang; Yanlin Chen; Qian Hu; Yi-Lin Liu; Jie Wang; Qingyi Zeng (Chemical Engineering Journal, 2026)

Intensive study on the ultra-high capacity, selectivity and stability in uranium immobilization by hydroxyapatite - Yanlin Chen; Qingyan Zhang; Xijun Fu; Shuaishuai Guo; Qingyi Zeng (Chemical Engineering Journal, 2025)

Establishment and characterization of immortalized Tibetan pig skeletal muscle satellite cells for cultured meat applications - Yangmin Wang; Xikui Tong; Yunhui Fu; Yiying Chen; Xinyang Chen; Yuxi Li; Tongxi Diao; Wenyun Zheng; Yanlin Wang; Xingyuan Ma (Food Bioscience, 2025)

Effects of nanoactive fluids on water wettability reversal of shale: Implications for CO2 geo-sequestration - Chenqing Shang; Jiren Tang; Wenchuan Liu; Yanlin Liu; Yunzhong Jia; Yongjun Xiao; Wenyu Fu; Qi Cheng (Process Safety and Environmental Protection, 2024)

Sustainable microwave-heating healing asphalt concrete incorporating functional aggregates and waste ferrite - Dong Lu; Chaoliang Fu; Xi Jiang; Zhaojie Chen; Fulin Qu; Yanlin Huo; Zhen Leng; Jing Zhong (Transportation Research Part D: Transport and Environment, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Impacts of replacing dietary fish meal with poultry by-product meal on growth, digestive enzymes and gut microbiota, biomarkers of metabolic and immune response, and resistance to Vibrio challenge in abalone (Haliotis discus hannai) - Zhenhua Wu; Xiaojun Yu; Yonghao Fu; Jinshu Guo; Mingzhu Pan; Yanlin Guo; Jiahuan Liu; Kangsen Mai; Wenbing Zhang (Aquaculture, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Construction of a portable immunosensor for the sensitive detection of carbendazim in agricultural products using a personal glucose meter - Haoran Liu; Longyingzi Xie; Yiwen Wang; Yanlin Liu; Ruijie Fu; Yongliang Cui; Qiyang Zhao; Chengqiu Wang; Bining Jiao; Yue He (Food Chemistry, 2023)

Energy-based cloud detection in multispectral images based on the SVM technique - Yanlin Sui; Bin He; Tianjiao Fu (International Journal of Remote Sensing, 2019)

Identification, characterization of selenoprotein W and its mRNA expression patterns in response to somatostatin 14, cysteamine hydrochloride, 17β-estradiol and a binary mixture of 17β-estradiol and cysteamine hydrochloride in topmouth culter (Erythroculter ilishaeformis) - Haiyan Dong; Wenbo Chen; Chao Sun; Jianwei Sun; Yanlin Wang; Chao Xie; Qianwen Fu; Junjie Zhu; Jinyun Ye (Fish Physiology and Biochemistry, 2017)